DETERMINAN SHARIA COMPLIANCE DALAM PENGUMPULAN ZIS MELALUI BUDAYA KENCLENG - Holilur Rahman; Mujibno Mujibno; Idha Suhartatik; Abdullah Muhammady (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
This article aims to reveal the determinants of sharia compliance in collecting Zakat, Infaq and Shadaqah (ZIS) funds through the charity box culture (kencleng ) at the Sumenep Zakat, Infaq and Shadaqah Amil Institute (LAZISNU) involving non-Muslims. Collecting ZIS through kencleng involving non-Muslims is problematic. This research examines the kencleng culture in collecting ZIS as a factor that determines sharia compliance. This article argues that fundrasing through kencleng culture involving non-Muslims in Lazisnu Sumenep city fulfills sharia compliance. The article is based on qualitative research with a case study approach. Data was collected through in-depth interviews, observation and document analysis. Research informants consisted of LAZISNU administrators, kencleng distributors, shops, and ZIS donors. This article identifies four determinants of sharia compliance in fundraising donations through kencleng culture at LAZISNU Sumenep: First, the generosity in fundraising is the initial motivation for participation in collecting ZIS. Second, the aqad factor of donations through kencleng as philanthropy determines the validity of ZIS. Third, regular monitoring and supervision by Sharia Supervisory Board (DPS) even though administratively it shows that standard operating procedures (SOP) are being implemented. Fourth, kencleng socio-cultural norms help promote ZIS collection. The contribution of this research is the importance of strengthening sharia commitment, effectiveness, community participation and promotion as an effort to optimize ZIS collection.